Stereotactic amygdalohippocampectomy for temporal lobe epilepsy: promising results in 16 patients - Kalina, Miroslav; Liščák, Roman; Vojtěch, Zdeněk; Adámková, Eva; Procházka, Tomáš; Marečková, Iva; Vladyka, Vilibald (Epileptic disorders, 2007)
OBJECTIVES: Minimally invasive procedures for treating temporal lobe epilepsy have been investigated recently, namely stereotactic and gamma knife amygdalohippocampectomy (AHE). However, the results are not fully satisfactory. Our aim was to evaluate efficacy and side-effects of stereotactic AHE mimicking the neurosurgical procedure in terms of extent of the lesion. METHODS: 16 consecutive patients were assessed using VEEG, MRI, FDG-PET and WADA test. All had definite pharmacoresistant medial temporal lobe epilepsy. The stereotactic AHE was performed on the Leksell stereotactic system. All lesions exceeded 40 mm along the long axis of the hippocamus. RESULTS: Seizure outcome was favourable on one year follow-up: 12 patients (75%) were seizure-free (Engel I), three (19%) were Engel II, and one (6%) was Engel III. Side-effects were mild, lasting up to 7 days: cephalea, meningeal syndrome with sterile CSF in three subjects, and CSF leak lasting up to 3 days in seven subjects. CONCLUSION: Stereotactic AHE encompassing sufficient volume of the amygdalohippocampal complex appears to be safe, effective, and free from long-term side-effects.
Keywords: financování organizované; dospělí; Magnetic Resonance Imaging; Drug Resistance; Female; hipokampus; stereotaktické techniky; Adult; ženské pohlaví; Epilepsy, Temporal Lobe; léková rezistence; radiofarmaka; fluorodeoxyglukosa F18; lidé; magnetická rezonanční tomografie; epilepsie temporálního laloku; Neurosurgical Procedures; neurochirurgické výkony; Financing, Organized; Male; amygdala; Amygdala; Radiopharmaceuticals; Hippocampus; lidé středního věku; pozitronová emisní tomografie; Fluorodeoxyglucose F18; mužské pohlaví; Stereotaxic Techniques; Middle Aged; Positron-Emission Tomography; Humans